Indígena y abogado: el caso de José Domingo Choquehuanca de Azángaro - Sala I Vila, Nuria (2018)
This essay focuses on the political thought of José Domingo Choquehuanca, a member of a family of indigenous nobles that, from the colonial period and the first Republican century, occupied administrative, judicial, and political posts in their regional power center. Thus, José Domingo found himself in a key transitional period between the Spanish colonial system and the formation of the republic; a member of a group of intellectuals who laid a liberal juridical foundation for the newly-born nation. This study suggests that Choquehuanca preserved symbols of his seigneurial authority while following the constant changes of a politically and socially tumultuous Peru, which informed the development of his political thought in a new context of meritocracy and equality.